The Power of the Public Defender Experience: Learning by Fighting for the Incarcerated and Poor - Patrick C. Brayer (Washington University Journal of Law & Policy, 2017)
This Essay discusses how public defender apprenticeships impact law students and help mold their future careers. Brayer discusses the tangible advantages that the apprenticeship imparts on students as well as the transferable skills that students gain. Brayer then analyzes the internal and professional growth of students that participate in this apprenticeship. Brayer situates this growth within the context of Chief Justice John Marshall’s own similar experience, arguing how the public defender experience focuses and matures aspiring lawyers.
Keywords: public defender; apprenticeship; law students; Washington University School of Law; clinic; Criminal Justice Clinic; Chief Justice John Marshall; training; teaching